Design Tactics for Urban Places: Fragmentation and malleability in attachment to contested and changing cities. (2nd January 2018) - Creagh, Robyn
Abstract: Understanding place as process offers an alternative to the reproduction of places as static objects and the resultant problematic exclusion of multiple other narratives. This paper builds on the work of Lefebvre, de Certeau and Massy to develop design tactics for engaging with places as dynamic, plural and interconnected. This paper describes and analyses an original exhibition of large scale participatory artworks which explored the role of travel histories and memory for the author's sense of place in Perth, Western Australia. Reflection on this exhibition supports the argument that perceiving an urban location as a place depends on the opportunity for inhabitants to layer in their own contributions, and crucially, to observe change brought about by these actions and those of others. This paper concludes by offering fragmentation and malleability as tactics for further design and research within urban development, re-development, and placemaking projects.